Design of Loran-C receiving antenna with high-performance - Gao Jiuxiang; Yuan Yanning; Shi Zhensheng; Xi Xiaoli (Dianzi Jishu Yingyong)
A kind of magnetic antenna with order series multi-layer coils is made for improving the receiving ability of the Loran-C magnetic antenna. The signal-to-noise ratio and sensitivity of order series multi-layer coil magnetic antenna are derived theoretically. Final designed magnetic antenna size is 150 mm×150 mm. It can receive the completed and clear Loran-C signal in far-field test. Under the same signal conditioning circuit conditions, compared with single layer and single group of coils magnetic antenna, order series multi-layer coils magnetic antenna receives a voltage signal of 3.47 V, and the signal-to-noise ratio is 30.87 dB. The sensitivity and signal-to-noise ratio are improved 82.42% and 63.20% respectively. The proposed method improves the receiving performance of the Loran-C magnetic antenna, which is of great significance to the application of the Loran-C system in positioning.